Penerapan Metode Role Playing untuk Meningkatan Kemampuan Sosial Emosional Anak Usia 5-6 Tahun di TK IT Tahfidz Insan Mulia - Wildani, Wildani; Nurmawati, Nurmawati; Nasution, Inom (Darul Yasin Al Sys, 2024)
This study aimed to determine the improvement of the social-emotional abilities of kindergarten students in group BI at TK IT Tahfidz Insan Mulia Kota Tebing Tinggi through the application of role playing learning model. This type of study is classroom action research which is carried out as many as two cycles and each cycle is carried out with three meetings. The subject of this study were 26 students of group BI with totaling 13 boys and 13 girls in the academic year 2023/2024. The mothod of data collection regarding social-emotinal abilities was collected by observation method. The result of data analysis showed that there was achievement in student's social-emotional abilities with the application of role playing learning model in cycle 1 was included in the category of developing very well in Indonesian called Berkembang Sangat Baik (BSB) still 4% and achievement in cycle II to 54% in the category of developing as expected in Indonesian called Berkembang Sesuai Harapan ( BSH).